1995
DOI: 10.1007/bf00232734
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of benzyladenine in Spathiphyllum floribundum ‘Schott Petite’ in relation to acclimatisation problems

Abstract: In Spathiphyllum floribundum 'Petite', which was cultured on medium containing benzyladenine (BA), uptake of this cytokinin and its conversion to 9-ß-D-ribofuranosyl-benzyladenine (9R-BA) or 9-ß-glucopyranosyl-benzyladenine (9G-BA) was monitored. BA and extremely large quantities of 9G-BA were exclusively located in the basal part of the plant (callus and meristems). 9R-BA was found in the basal part, the petioles and the leaf blades. After an acclimatisation period of 9 weeks the plants still contained high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
1
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 10 publications
2
59
1
1
Order By: Relevance
“…For the ecological purpose of maintaining genetic diversity and achieving cost-effective commercial micropropagation, the efficient in vitro production and ex vitro acclimatization of a large number of sea oats genotypes is essential. Benzyladenine (BA), the most widely used cytokinin incorporated into culture media to promote axillary shoot production, often has deleterious effects on subsequent rooting and ex vitro acclimatization (Pospíšilová et al 1992;Werbrouck et al 1995). Currently, BA is the only effective cytokinin that promotes in vitro shoot production of sea oats (Philman and Kane 1994).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the ecological purpose of maintaining genetic diversity and achieving cost-effective commercial micropropagation, the efficient in vitro production and ex vitro acclimatization of a large number of sea oats genotypes is essential. Benzyladenine (BA), the most widely used cytokinin incorporated into culture media to promote axillary shoot production, often has deleterious effects on subsequent rooting and ex vitro acclimatization (Pospíšilová et al 1992;Werbrouck et al 1995). Currently, BA is the only effective cytokinin that promotes in vitro shoot production of sea oats (Philman and Kane 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, BA is the only effective cytokinin that promotes in vitro shoot production of sea oats (Philman and Kane 1994). Werbrouck et al (1995) correlated reductions in rooting and acclimatization of Spathiphyllum floribundum (peace lily) shoots produced on BA-supplemented medium with the accumulation of the BA metabolite 9-B-glucopyransosyl-benzyladenine (9G-BA) at the base of plantlets in vitro. Hydroxylated analogs of BA have been proposed as alternative cytokinin substitutes to BA in plant tissue systems (Werbrouck et al 1996;Strnad 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that another naturally occurring aromatic cytokinin, mT, due to its faster degradation in plant tissue, did not have negative effect on rhizogenic capacity [Werbrouck et al 1995, Wojtania et al 2011. In our study, however, neither lowering the cytokinin concentration nor replacement of BA to mT, which is BA derivative, positively influenced rooting.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of benzyladenine may be due to N 7 -and N 9 -glycosilation or alanin conjugation resulting in biologically inactive but chemically very stable derivatives. The slow release of benzyladenine from its derivatives might cause the inhibition of rooting as proved in other plant species (Werbrouck et al, 1995).…”
Section: Introductionmentioning
confidence: 92%